Analysis of production characteristics and engineering measures for deep coalbed methane wells in the Ordos Basin - Zhengyan, Zhao; Xiaohua, Tan; Xianwen, Wang; Wei, Tian; Youliang, Jia (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Given the significant differences in gas accumulation modes, coal reservoir characteristics, and gas preservation conditions for ultra-deep coalbed methane (vertical depth > 3000 m, measured depth > 5000 m), their production characteristics, flowback patterns, and flow phase classifications also vary greatly. Additionally, there are limitations in the production technologies applicable to deep reservoirs. To explore the relationship between the production characteristics of deep coalbed methane and medium-shallow coalbed methane, as well as to investigate suitable technologies for deep coalbed methane, this paper uses Well Q1 as an example and conducts research and analysis based on reservoir engineering theory. It is believed that in the vertical section of Well Q1(The depth is generally less than 3000m), the flow pattern transitions from bubbly flow to slug flow in the early stage, and with reduced water production, it is predicted to transition from transitional flow to annular flow in the later stage. In the inclined section (The depth is generally between 3000 and 4000m), slug flow predominates most of the time, while in the horizontal section (The depth is generally greater than 4000m), the flow evolves from elongated bubble flow to slug flow in the early stage, from elongated bubble flow to stratified smooth flow in the middle stage, and remains in the stratified smooth flow zone in the later stage. Furthermore, it is proposed that the insertion depth of Well Q1 should be correlated with the well deviation angle, gas production rate, and water production rate. From the perspective of gas-water ratio optimisation and energy efficiency, there should be an optimal timing for tubing insertion.